An unconventional adaptive flutter suppression actuation system: From modeling to experimentation. (May 2017) - Cassaro, Mario; Battipede, Manuela; Gili, Piero; Marzocca, Pier
This article contributes to the definition of an unconventional actuation system coupled with an adaptive control algorithm, it is intended specifically for slender/highly flexible wings flutter suppression. The design and validation process of the novel actuation architecture is presented together with the performance analysis of the post-flutter dynamics control. Robustness of the overall control architecture is verified with respect to the uncertainties deriving from the unpredictable degradation of the structural properties. The proposed actuation system is based on a row of multiple mini-spoilers, located in proximity of the leading edge and coordinated by a modified model reference adaptive control algorithm. The spoiler configuration is optimized by computational fluid dynamics numerical simulation, whereas the aerodynamic database is derived by wind tunnel tests on the prototype by means of a six-axes force balance. The resulting aeroelastic mathematical model is then used to implement and validate the adaptive control algorithm for a wide range of conditions, from on-design flutter speed and nominal structural stiffness to post-flutter speed and reduced structural stiffness. The two degree of freedom aeroelastic model is successfully controlled in all conditions. This article aims at defining a robust procedure for aeroelastic phenomena control system design, which employs a synergy of modeling, simulation, and experimental approaches. Pertinent conclusions are discussed in the final section of the article.